PEMBUATAN AKTA PEMBAGIAN HAK BERSAMA DALAM PERALIHAN TANAH KARENA PEWARISAN DI KOTA BUKITTINGGI - Beatrix Benni; Kurniawarman Kurniawarman; Anisa Rahman (STIH Putri Maharaja, 2019)
The analysis of Article 51 PP 24/1997 explains the registration of the transfer of rights as yet there is no inheritance distribution, so that the inheritance is still in joint ownership, when the right holders agree to share their rights into the rights of each right holder then inheritance based on a joint rights deed made by PPAT. Article 111 paragraph (4) and paragraph 5 PMNA / KBN 3/1997 explain that at the time of registration of the transfer of rights if the heirs agree to give rights to inherited land to one person, it can be proven by deed of deed in the form of deed Notary or in the form deed under the hand. Implementation in Bukittinggi, registration of the transfer of rights cannot use the deed of distribution of inheritance which is carried out in conjunction with the process of inheritance but must be based on the deed of distribution of joint rights made by PPAT. The research issue raised in this article is to find out how the drafting of sharing of joint rights in the transfer of land due to inheritance? how is the distribution of inheritance to land as a joint asset in the family? The approach used by researchers is an Empirical Juridical approach. The results showed that the sharing of shared rights was made with a joint deed of rights distribution by PPAT with due observance to the provisions of Article 51 of Government Regulation Number 24 of 1997. Distribution of inheritance to land as shared assets in the family in the city of Bukittinggi was based on an agreement between the heirs to give up their rights - however, as to who the heirs are entitled to, the land is based on the Civil Code applicable to the testator.